STUDENTS’ WILLINGNESS TO COMMUNICATE (WTC) IN ENGLISH LANGUAGE : A CASE STUDY - Rozal, Edi; Andriani, Reni; Nadila, Sintya (JR-ELT (Journal of Research in English Language Teaching), 2020)
This research primary objective is to identify the factors influencing students' propensity to communicate in English at MTs N 8 Muaro Jambi. The second objective is to determine how willing pupils are to communicate in English at MTs N 8 Muaro Jambi. The qualitative descriptive method was utilised in the study's design. This research was conducted with ninth-grade students from MTs N 8 Muaro Jambi. This research data was collected through interviews, and based on the findings and discussions, a number of factors influenced students' propensity to communicate in English. There are two different categories of factors: internal and external. Regarding internal factors, the students' willingness is affected by their self-willingness. Regarding external factors, the teacher, the classroom environment, and the effect of the topic influence students' resolve. The most influential of these factors are self-will and classroom environment. The majority of students stated that they are eager to use English when communicating. The students' propensity to communicate in English at MTs N 8 Muaro Jambi is divided into two levels, namely high level and medium level, based on the findings of the second research question. Students believe that using English is essential for various purposes. In this study, the researcher suggests that students can increase their willingness to communicate in English.